TRANSLATION METHOD USED IN DELI MALAY AND SERDANG MALAY FOLKLORES FROM INDONESIAN TO ENGLISH - RIA RESTIKA; MASITOWARNI SIREGAR; LIDIMAN SAHAT M SINAGA (LINGUISTICA, 2021)
This study aimed to determine the many types of translation methods, how they were employed in the translation of the folklores "Deli Malay" and "Serdang Malay" from Indonesian to English, and why the translators used the prevailing types in these folklores. The descriptive qualitative method was used to perform this research. The data was gathered from a folklore book and an interview with the folklores' translator. Descriptive qualitative research is the method used to analyze the data. The findings of this study revealed that literal translation accounted for 39 sentences (16%), faithful translation accounted for 23 sentences (9%), semantic translation accounted for four sentences (2%), adaptation translation accounted for seven sentences (3%), free translation accounted for 158 sentences (64%) and communicative translation accounted for 16 sentences (6%). A total of 247 sentences were extracted from the data. Because he did not follow any theories or methods of translation when translating the texts, the translator utilized free translation as the dominating method. Instead, he evaluated the translations' target audience, youngsters, and made them acceptable and simple to understand.